2010
DOI: 10.1021/ac100852z
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Resonance Energy Transfer between Quantum Dots and Graphene Oxide for Sensing Biomolecules

Abstract: This work designed a novel platform for effective sensing of biomolecules by fluorescence resonance energy transfer (FRET) from quantum dots (QDs) to graphene oxide (GO). The QDs were first modified with a molecular beacon (MB) as a probe to recognize the target analyte. The strong interaction between MB and GO led to the fluorescent quenching of QDs. Upon the recognition of the target, the distance between the QDs and GO increased, and the interaction between target-bound MB and GO became weaker, which signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
458
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 746 publications
(481 citation statements)
references
References 50 publications
13
458
0
4
Order By: Relevance
“…(24). This effect has also been verified experimentally by Dong et al,32 where upon integrating a molecular beacon to a CdTe QD, it was found that the fluorescence quenching due to graphene is modified. We also note that at certain values of probe detuning, say for example, δ 2 ≈ ±1.5 μeV, the sensitivity of the energy transfer rate to the change in dielectric constant is quite high.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…(24). This effect has also been verified experimentally by Dong et al,32 where upon integrating a molecular beacon to a CdTe QD, it was found that the fluorescence quenching due to graphene is modified. We also note that at certain values of probe detuning, say for example, δ 2 ≈ ±1.5 μeV, the sensitivity of the energy transfer rate to the change in dielectric constant is quite high.…”
Section: Resultssupporting
confidence: 66%
“…21,22,[26][27][28][29] Recently, experimental research on graphene has been extended to the fabrication and study of QD-graphene nanostructures. [30][31][32][33][34] For example, a CdS QD-graphene hybrid system has been synthesized by Cao et al, 30 in which a picosecond ultrafast electron transfer process from the excited QD to the graphene matrix was observed using time-resolved fluorescence spectroscopy. Chen et al 31 have fabricated CdSe/ZnS QDs in contact with single-and few-layer graphene sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Since NCs are naturally conjugated to DNA after the synthesis, a molecular beacon setup is an obvious method of using these NCs as a fluorophore substituent. Similar applications have already been demonstrated using semiconductor quantum dots [86,87], although it needs to be noted that it is quite difficult to conjugate DNA to an as-synthesized quantum dot. Since DNA is already a part of the NC structure, it is unnecessary to perform additional conjugation reactions.…”
Section: Molecular Beaconsmentioning
confidence: 75%
“…Graphene oxide (GO) is a general quencher for a diverse range of fluorophores, including semiconductor quantum dots [87,89,90]. DNA can be adsorbed by GO and also desorb by adding its cDNA to form a duplex [91].…”
Section: Molecular Beaconsmentioning
confidence: 99%
“…GO strongly adsorbs nonstructured single-stranded (ss-DNA), while adsorption of well-folded or double-stranded (ds) DNA is disfavored. Combined with its superior fluorescence quenching ability, a number of sensors have been prepared to detect metal ions, 31,32 small molecules, 13,33,34 proteins, 35 DNA, [36][37][38][39][40][41] and cells. 42 Most of these sensors were designed using a scheme shown in Figure 1A.…”
Section: Introductionmentioning
confidence: 99%